Fatigue Resistance of Typical Fatigue Prone Riveted Steel Railway Bridge Structural Detail - Vican, Josef; Gocal, Jozef; Jost, Jozef (Communications - Scientific Letters of the University of Zilina, 2011)
There are still a lot of riveted steel railway bridges built in the first half of 20th century in service, and so it is important to pay attention to their evaluation. Their fatigue resistance represents one of the most determining factors on decision making process oriented to possibility of their further exploitation after finishing their planned service life. The standard method of fatigue assessment according to Eurocode EN 1993-1-9 is based on categorization of structural details, which reflects their predisposition to fatigue failure. The paper deals with laboratory investigation of the riveted connection of stringer to cross beam of a railway bridge deck. This structural detail is typical by frequent occurrence of fatigue cracks, but its categorization according to standard mentioned above is at least questionable. In order to investigate and define the fatigue category of this detail more properly, the laboratory tests on specially adapted specimens were performed.
Keywords: bridge fatigue lifetime; fatigue resistance; fatigue detail categorisation; stringer to cross-beam connection